The Evaluation of The Effectiveness of Nosocomial Infection Control Strategies on Antibiotic Resistance at Hospital X - Studiviani Dwi Binuko, Raafika; Sutrisna, Em; Masyita Dewi, Listiana; Diana Risanti, Erika (LPPM Universitas Duta Bangsa Surakarta, 2024)
The primary issue in this study is the high incidence of nosocomial infections, indicating the need to evaluate the effectiveness of infection control strategies. The objective of this study is to analyze the relationship between various infection control strategies and the incidence of nosocomial infections, along with other related factors. The method used is a correlation analysis between infection control strategies, the incidence of nosocomial infections, antibiotic resistance rates, hygiene standards, patient age, patient gender, and the number of beds. The analysis results show a perfect positive correlation between infection control strategies and the incidence of nosocomial infections (r = 1.00), indicating that the implementation of effective strategies can significantly reduce nosocomial infections. A moderate positive correlation was found between infection control strategies and antibiotic resistance rates (r = 0.50) as well as hygiene standards (r = 0.52), suggesting that good strategies can also reduce antibiotic resistance and improve cleanliness. Conversely, the correlation between infection control strategies and the number of beds (r = 0.06) and patient age (r = -0.09) is weak, indicating that these factors do not significantly influence the effectiveness of the strategies. These findings underscore the importance of focusing on hygiene and infection control policies to reduce nosocomial infections and antibiotic resistance.